Effect of Giving Chicken Feather Flour as Supplementary Feed For Weight Gain Broiler Chicken (Gallus domesticus L) - M Aziz Rizki; Asiah Asiah; Khairil Khairil; Abdullah Abdullah; Iswadi Iswadi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Broiler chickens are superior breeds of chickens resulting from crosses from chicken breeds that have high productivity, especially in producing meat. This research aims to identify the effect of the accumulation of chicken feather meal as a bonus feed on the weight gain of broiler chickens. The research procedure used was an Experiment with 4 treatments and 6 replications, namely P0 = control (100% natural bran feed), P1 = 95% natural bran feed + 5% chicken feather flour, P2 = 90% natural bran feed + chicken feather flour 10%, P3 = 85% natural bran feed + 15% chicken feather flour. Information was analyzed by Analysis of Variance (ANOVA). The results of the research show that giving chicken feather flour as an additional feed for weight gain of broiler chickens has a significant effect on weight gain of broiler chickens in the second week, fourth week, or sixth week. The conclusions of the research are: Chicken feather flour affects the weight gain of broiler chickens.Keywords: Feather flour, feed, broiler chickens Ayam broiler ialah unggas tipe ras terbaik hasil modifikasi dari genus ayam yang dapat produktivitas tinggi, paling utama dalam memperoleh daging. Riset ini bertujuan mengenali pengaruh akumulasi tepung bulu ayam selaku pakan tambahan mempengaruhi pertambahan bobot tubuh ayam broiler. Tata cara riset yang digunakan merupakan Ekperimen dengan 4 perlakuan serta 6 ulangan ialah P0 = kontrol (pakan dedak 100%), P1= pakan dedak 95%+ tepung bulu ayam 5%, P2= pakan dedak 90%+ tepung bulu ayam 10%, P3= pakan dedak 85%+ tepung bulu ayam 15%. Data dianalisis dengan Analisis Varian (ANAVA). Hasil riset membuktikan kalau pemberian tepung bulu ayam selaku pakan tamabahan buat pertambahan bobot ayam broiler berpengaruh nyata kepada penambahan berat badan ayam broiler di pekan kedua, pekan keempat, ataupun pekan keenam. Kesimpulan riset merupakan: Tepung bulu ayam mempengaruhi terhadap pertambahan berat tubuh ayam broiler.Kata kunci: Tepung bulu ayam, pakan, ayam broiler.